Altered Brain Regional Homogeneity Following Electro-Acupuncture Stimulation at Sanyinjiao (SP6) in Women With Premenstrual Syndrome - Pang, Yong; Liu, Huimei; Duan, Gaoxiong; Liao, Hai; Liu, Yanfei; Feng, Zhuo; Tao, Jien; Zou, Zhuocheng; Du, Guoxiang; Wan, Rongchao; Liu, Peng; Deng, Demao (Frontiers in Human Neuroscience, 2018)
Background: Premenstrual syndrome (PMS) is a menstrual cycle-related disorder involved in brain functional dysregulation. Acupuncture is an effective alternative therapy for treating PMS, and sanyinjiao (SP6) is one of the most common acupoints used for improving the symptoms of PMS. However, it is not clear whether or not the potential mechanisms of acupuncture on PMS is related to acupuncture effects on modulating the brain of PMS. The aim of this work was to investigate the specific brain response patterns in PMS patients induced by acupuncture at SP6. Methods and Materials: 23 females with PMS were enrolled in this study. All patients received a 6-min electro-acupuncture stimulation (EAS) at SP6 and underwent two 6-min resting state fMRI scans before and after EAS. Regional homogeneity (ReHo) method was used to examine response patterns of the whole brain induced by EAS at SP6 with comparison to the resting state of pre-EAS. This study was registered at http://www.chictr.org.cn, the Clinical Trial Registration Number was ChiCTR-OPC-15005918, and the registration number was achieved at 29/01/2015. Results: Compared to pre-EAS, EAS at SP6 elicited the decreased ReHo values in the bilateral precuneus, left middle frontal cortex and right inferior frontal cortex, while increased ReHo values in the bilateral insula, bilateral thalamus, left putamen and right primary somatosensory cortex. Conclusions: The current study provide imaging evidence to support that SP6-related acupuncture stimulation could modulate the abnormal neural activity in PMS patients. Our study may partly interpret the neural mechanisms of acupuncture at SP6 which is used to treat PMS patients in clinical.